RECENT ADVANCES IN SIMULATING LANDSLIDE AND DEBRIS FLOW - Wei Wu (Acta Polytechnica CTU Proceedings, 2021)
This paper summarizes the outcome of a research project funded by the European Commission on the simulation of landslide and debris flow. The numerical techniques adopted include the mesh-based method (FEM), the point-based method (SPH) as well as a hybrid method (Lattice-Boltzmann Method and DEM). Centrifuge model tests were carried out for the purpose of validation.